2009
DOI: 10.1002/ejoc.200900236
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Designs and Syntheses of Organic Dyes for Dye‐Sensitized Solar Cells

Abstract: Dye‐sensitized solar cells (DSSCs) based on organic dyes adsorbed on nanocrystalline TiO2 electrodes have received considerable attention because of their high incident solar light‐to‐electricity conversion efficiency and low cost of production. A number of organic dyes have so far been developed, and the relationship between their chemical structures and the photovoltaic performances of DSSCs based on the dyes has been examined. To create high‐performance DSSCs, it is important to develop effective organic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
375
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 594 publications
(380 citation statements)
references
References 197 publications
3
375
1
1
Order By: Relevance
“…In particular, donor-acceptor p-conjugated (D-p-A) dyes are considered one of the most promising classes of metal-free organic sensitizers [3][4][5][6]. Zhang et al [7] reported that DSSCs based on a D-p-A dye (C217) show a power conversion efficiency of 9.8%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, donor-acceptor p-conjugated (D-p-A) dyes are considered one of the most promising classes of metal-free organic sensitizers [3][4][5][6]. Zhang et al [7] reported that DSSCs based on a D-p-A dye (C217) show a power conversion efficiency of 9.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The most useful donor group is triphenylamine (TPA), but other donor groups have also been reported [2][3][4][5][6]. The widely used acceptor and anchor group is cyanoacrylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…As B(C 6 F 5 ) 3 was added to the solutions of pDTSTPyT and pDTSPy in benzene, the solution changed color from red to purple. Simultaneously, the absorbance of the UV-Vis bands of the parent polymers decreased, and new bands appeared at longer wavelengths, which became more intense with increasing concentration of B(C 6 F 5 ) 3 . This result is in good agreement with the previously reported [15][16][17][18] optical properties of similar complexes of pyridinecontaining polymers with borane, and it clearly indicates that complex formation reduces the polymer band gap, thereby potentially allowing for fine tuning of the electronic states.…”
Section: Optical Propertiesmentioning
confidence: 98%
“…Complex formation with B(C 6 F 5 ) 3 Complex formation between the polymers and B(C 6 F 5 ) 3 was monitored by UV-Vis absorption spectrophotometry, as shown in Figure 2. As B(C 6 F 5 ) 3 was added to the solutions of pDTSTPyT and pDTSPy in benzene, the solution changed color from red to purple.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation